Pengaruh Persepsi Nilai dan Kepercayaan Terhadap Loyalitas Pengguna dengan Kepuasan Pengguna Game Roblox Sebagai Mediasi - Achmad Zaky Maulana; Ryna Parlyna; Fildzah Shabrina (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid growth of online games driven by digital economic ecosystems has intensified the use of virtual currencies and microtransaction activities, such as Robux purchases within the Roblox platform. This phenomenon gives rise to issues concerning users’ perceived value and trust, which potentially affect their levels of satisfaction and loyalty. This study seeks to examine the influence of perceived value and trust on customer loyalty, with customer satisfaction serving as a mediating variable among Roblox game users. A quantitative research design was adopted by distributing an online survey to 100 respondents from the Faculty of Economics and Business, Universitas Negeri Jakarta, who had prior experience purchasing Robux. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) technique. The findings demonstrate that perceived value and trust exert positive and significant effects on both customer satisfaction and customer loyalty. Furthermore, customer satisfaction is found to have a positive and significant impact on customer loyalty. The mediation analysis reveals that customer satisfaction significantly mediates the relationship between perceived value and customer loyalty, while it does not mediate the effect of trust on customer loyalty. These results indicate that customer loyalty among Roblox users is predominantly shaped by perceived value and trust through direct pathways, whereas customer satisfaction functions selectively as a mediating mechanism.